(untitled) (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2026)
Research on financial literacy and perceived trust in general insurance purchase intention has not been widely conducted. However, such research can help insurance companies improve their services and sell the types of products needed by the public. The independent variables used in this study are the level of financial literacy and perceived trust in general insurance products. Meanwhile, the dependent variable is the interest in purchasing general insurance products. The sampling technique used in this study was purposive sampling with several specific considerations: a minimum age of 21 years, domiciled in Jakarta and Yogyakarta, knowing or having received information about general insurance, having a minimum income of Rp 3,000,000 per month, and not having a general insurance product. Using SPSS software, the results showed that the variables of financial literacy and perceived trust also had a significant positive effect on the interest in purchasing general insurance products, both partially and simultaneously. These two variables can explain the variable of buying interest in general insurance by 47.1